Electrocardiographic signs of impaired depolarization (fragmented QRS, early ventricular repolarization, etc.) as markers of left ventricular systolic dysfunction - M. S. Gordeeva; I. A. Serdiukova; A. S. Krasichkov; E. V. Parmon (Российский кардиологический журнал, 2022)
Aim. To study the relationship between a decrease in left ventricular (LV) ejection fraction (EF) and conventional electrocardiographic (ECG) signs associated with myocardial structure changes (pathological Q wave, ventricular arrhythmias), and relatively novel and less studied (fragmented QRS (fQRS), early ventricular repolarization (EVR)) and to evaluate their significance for identifying patients with mildly-reduced EF (mrEF).Material and methods. The study included 148 patients who were treated and examined at the Almazov National Medical Research Center. During the ECG analysis, fQRS, EVR, pathological Q wave, and ventricular arrhythmias (VAs) were assessed. Echocardiography data were analyzed. Statistical processing was carried out, including Fisher and chi-squared test, as well as correlation and ROC analysis.Results. Depending on the EF level, patients were divided into three groups: group 1 — patients with reduced EF (rEF) (<40%); group 2 — patients with mrEF (40-49%); group 3 — patients with preserved EF (pEF) (>50%). In the 1st group (with rEF), fQRS was registered in 16 (51,6%) patients, in the 2nd (with mrEF) — in 13 (44,8%), in the 3rd (with EF >50%) — in 16 (18,2%). Pathological Q wave was detected in the 1st group (rEF) in 20 (65%) patients, in the 2nd (mrEF) — in 10 (35%); in the 3rd (pEF) — in 15 (18%) (p<0,001). ROC analysis found that fQRS is more important for identifying patients with mrEF. In the 1st group (rEF), EVR was registered in 2 (6,5%) patients, in the 2nd (pEF) — in 2 (6,9%), in the 3rd (EF>50%) — in 11 (12,5%); the differences were not significant (p=0,5). The relationship of EVR, the number of PVCs and the presence of ventricular tachycardia with EF was not revealed.Conclusion. FQRS is significantly more often observed with a decrease in EF and may be a marker of an mildly-reduced EF. There were no significant correlations between EVR and EF. There was also no relationship between VAs and LV systolic dysfunction.